2016
DOI: 10.1002/jemt.22612
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional contrast dye for morphological research

Abstract: RIO proved to be a multifunctional contrast dye, which could be applied as an imaging biomarker for tissue vascularity or blood perfusion, for visualization of organ anatomy and for ex vivo validation of in vivo animal experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Human pathology has demonstrated alterations of the PVP under normal and diseased conditions [ 22 ], but it is impossible to expose the entry and exit of blood through this system. By staining red color to the liposoluble LPD [ 15 ] and using the BSS as a hydrosoluble alternative [ 14 ], this study has provided colorful histomorphologic evidence to support the previous “grayscale” findings [ 8 ] that indeed the PVP transported the arterially injected LPD and BSS into the PV branches. Although the PVP could be observed by the operator of the intravital microscope, the published black-white pictures failed to depict local structures, with labels or sketches needed to aid imagination [ 8 , 23 ].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Human pathology has demonstrated alterations of the PVP under normal and diseased conditions [ 22 ], but it is impossible to expose the entry and exit of blood through this system. By staining red color to the liposoluble LPD [ 15 ] and using the BSS as a hydrosoluble alternative [ 14 ], this study has provided colorful histomorphologic evidence to support the previous “grayscale” findings [ 8 ] that indeed the PVP transported the arterially injected LPD and BSS into the PV branches. Although the PVP could be observed by the operator of the intravital microscope, the published black-white pictures failed to depict local structures, with labels or sketches needed to aid imagination [ 8 , 23 ].…”
Section: Discussionsupporting
confidence: 65%
“…Technically, experimental studies on LPD proved challenging, because oily LPD becomes void in both paraffin and conventional lipid staining methods due to dissolution and/or washout of LPD by the applied organic solvents. By the prior coloration with Oil-red-O [ 15 ] and modified staining method, for the first time to our knowledge, we could microscopically identify the distribution of LPD in various locations of intrahepatic microcirculation. Furthermore, our experiment showed that both RIO and BSS took the same route in hepatic vasculature, making it possible to replace LPD by BSS to conduct standard morphology and quantification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations